Inovasi Rancang Bangun Mesin Multiguna untuk Meningkatkan Efisiensi Ekonomis dan Produktifitas Kerja Peternak di Kabupaten Tulungagung - Yoto; Didik Nurhadi; Agus Suyetno; Putri Ardista Nursisda Mawangi; Paryono Paryono; Muhammad Idris Effendi; Putrinda Inayatul Maula (G-Tech: Jurnal Teknologi Terapan, 2024)
This research developed a multifunctional machine to improve farm efficiency in Tulungagung, East Java, by combining grass chopper and corn grinder functions in a single device. The machine was tested at three rotational speeds (low, medium, high) and with three materials for chopping (Elephant Grass, Corn Stalks, Sugarcane Tops), as well as three sieve sizes (2mm, 4mm, 6mm) for grinding corn. The results showed that higher rotational speeds and larger sieve diameters increased output production. At high speed, the 6mm sieve produced up to 1385 kg of ground corn. This machine increases time and labor efficiency in feed preparation while reducing production costs through its multifunctional use. This innovation offers a practical solution for farmers in processing livestock feed, enhancing farm productivity and sustainability.